A preliminary sociolinguistic survey of Nubri Valley - Donohue, Cathryn (Nepalese Linguistics, 2019)
This paper reports results of a preliminary sociolinguistic survey that was carried out in Nubri Valley. Interviews were taken with people from throughout the valley. Some of the main findings are described here. The Nubri-perceived differences in dialect intelligibility and social status are discussed as well as the overall language vitality in the context of evolving social practices and observed language shift in the younger generations.